International market integration and market interdependence: evidence from China's stock market in the post-WTO accession period - He, Hongbo (2012)
The Chinese government has implemented a series of financial liberalisation policies in stock market after China’s accession into the WTO in 2001. However, it remains somewhat unclear whether and to what extent China’s financial liberalisation has influenced its stock market in the post-WTO accession period. This thesis examines this issue from the perspectives of international market integration and market interdependence. This thesis mainly includes three empirical studies: 1) gauging the degree of market integration by the weak-form measure, 2) measuring the degree of market interdependence by the multi-factor R-squared measure, as well as 3) examining the relationship between these two elements by the MWALD causality test and cointegration analysis. The first empirical study finds that China’s financial liberalisation might have largely decreased the stock market segmentation between China and the world in the period from July 2003 to June 2007, but this process has been interrupted by the global financial crisis in 2008. Meanwhile, only some of China’s financial liberalisation policies might be regarded as effective, such as the QFII programme, the first round of exchange rate reform and the QDII programme. The second empirical study regards that the stock market interdependence between China and the world has experienced three stages. These stages are: 1) the stationary stage from July 2001 to June 2003; 2) the increasing and steady stage from July 2003 to June 2006, which might be thanks to China’s financial liberalisation; as well as 3) an inverted U-shaped stage from July 2006 to December 2009, which might be attributed to China’s economy overheating in 2007 and to its economic stimulus plan in 2008. This third empirical study finds that there has been a unidirectional causal relationship from market integration to market interdependence, and a cointegration relationship between them. Market integration and market interdependence are found to be highly connected but different issues. Market integration is one, but not the only, determinant of market interdependence.